2019
DOI: 10.1111/fare.12356
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic–Racial Socialization Practices Among Latino Immigrant Families: A Latent Profile Analysis

Abstract: Objective To examine profiles of Latinx immigrant parents' use of ethnic–racial socialization (ERS) strategies, as well as demographic, cultural, and sociopolitical factors associated with those profiles. Background Few studies have examined ethnic–racial socialization strategies beyond cultural socialization among Latinx immigrant families. This study was designed to assess 6 ERS strategies: cultural socialization, promotion of mistrust, adapt (preparation for bias, avoidant coping), advocate (preparation for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 64 publications
2
60
0
Order By: Relevance
“…ERS practices are thought to be informed by parents’ individual and group experiences. For example, the more aware parents are of societal inequities impacting their ethnic–racial group, the more likely they are to alter their ERS practices to prepare their children to cope with future experiences of racial discrimination (Ayón, Ojeda, & Ruano, 2018; Ayón, Tran, & Nieri, 2019). With the current political climate, it is important to capture how Latinx parents’ practices include discussions about current issues and events within the broader sociopolitical context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERS practices are thought to be informed by parents’ individual and group experiences. For example, the more aware parents are of societal inequities impacting their ethnic–racial group, the more likely they are to alter their ERS practices to prepare their children to cope with future experiences of racial discrimination (Ayón, Ojeda, & Ruano, 2018; Ayón, Tran, & Nieri, 2019). With the current political climate, it is important to capture how Latinx parents’ practices include discussions about current issues and events within the broader sociopolitical context.…”
Section: Introductionmentioning
confidence: 99%
“…Further, parents adapt their ERS practices in response to sociopolitical conditions that may threaten their adolescents’ livelihood and well‐being (Ayón et al, 2019). It is possible that preparation for bias socialization conflates messages regarding broader political status and societal discrimination with those regarding the immediate risk of exposure to interpersonal discrimination youth may encounter in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…From a strength‐based perspective, protecting youth from these types of conversations and instilling hope in a better future, a strategy known as shift‐and‐persist (Christophe et al, 2019), may be intended to help youth frame and make meaning of stressors that are out of their control with optimism. Ayón, Tran, and Nieri (2019) similarly found that expressing gratitude, appreciation for diversity, and optimism for the future via advocacy and community empowerment were ways in which Latinx immigrant parents protected children from the harmful effects of anti‐immigration climate. There were many examples in our study of parents feeling proud of their citizen youth's ability to vote and rectify injustice, and of youth choosing not to think about or watch the election unfold.…”
Section: Discussionmentioning
confidence: 99%
“…Specific ethnic-racial socialization strategies often used by immigrant parents with their children include "adapt" (the preparation for bias and avoidant coping), and "advocate" (the preparation for bias and active coping). 30 Notably, immigrant SGM youth may fear doublediscrimination-stigma related to both their SGM and immigrant identities. 30 In addition, perhaps for recent immigrants to the United States, cultural norms experienced by Asian and Hispanic/Latinx parents do not align with those found in the United States, in particular toward SGM acceptance and identities.…”
Section: Id:c0040-p1285mentioning
confidence: 99%
“…30 Notably, immigrant SGM youth may fear doublediscrimination-stigma related to both their SGM and immigrant identities. 30 In addition, perhaps for recent immigrants to the United States, cultural norms experienced by Asian and Hispanic/Latinx parents do not align with those found in the United States, in particular toward SGM acceptance and identities. For example, stronger endorsement of machismo and the adherence to masculine norms in Hispanic/Latinx culture may contribute to lack of acceptance of SGM individuals among Hispanic/Latinx parents.…”
Section: Id:c0040-p1285mentioning
confidence: 99%